The Effectiveness of Metacognitive Therapy on Anxiety Sensitivity, Psychological Distress, and Pain Indicators in Female Students with Premenstrual Syndrome - Solgi, Zahra; Merati, Alireza; Yaseminejad, Parisa; Naderinobandegani, Zahra (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aims to investigating the effectiveness of Metacognitive Therapy (MCT) on anxiety sensitivity, psychological distress, and pain indicators in individuals with PMS.Methods and Materials: This semi-experimental study employed a pretest-posttest design with a control group and a two-month follow-up. The statistical population consisted of all female students diagnosed with PMS at Islamic Azad University of Kermanshah in 2024-2025. Thirty participants were selected using convenience sampling based on Fleiss’s formula and randomly assigned to two equal groups. The experimental group received ten weekly sessions of Metacognitive Therapy, each lasting 90 minutes. Data collection tools included the Premenstrual Symptoms Screening Tool (Steiner et al.), the Depression Anxiety Stress Scales (DASS; Lovibond & Lovibond), the Anxiety Sensitivity Index (ASI; Floyd et al.), the McGill Pain Questionnaire, and the Pain Acceptance Questionnaire (McCracken et al.). Data were analyzed using descriptive statistics and repeated measures ANOVA in SPSS-26.Findings: The findings revealed significant reductions in anxiety sensitivity (F=17.75, p=0.005, η²=0.61), pain intensity (F=6.18, p=0.009, η²=0.54), pain acceptance (F=10.70, p=0.014, η²=0.62), and psychological distress (F=43.45, p=0.001, η²=0.60) in the experimental group compared to the control group. These improvements were sustained at the two-month follow-up.Conclusion: Metacognitive Therapy is effective in reducing pain indicators, anxiety sensitivity, and psychological distress in individuals with Premenstrual Syndrome. This treatment plan may be recommended as a beneficial therapeutic approach for trauma and pain clinics.